Paradigmatic complementariness in variation studies - Hernández Campoy, Juan Manuel (Alicante Journal of English Studies / Revista Alicantina de Estudios Ingleses, 1999)
Despite the fact that linguistic change, as it is widely known, constitutes one of the great unsolved mysteries of linguistic science, and consequently a challenge to generations of linguists and philologists, we believe that the emergence of different trends in sociolinguistic research —regardless of their sophistication— and their subsequent disagreements are all evidence of the constantly increasing activity and vigour of variation studies. The importance of completing a combined approach to the phenomena of diffusion of language change from diverse perspectives, amongst which the dialectological, microsociolinguistic and geolinguistic ones must not be absent, is thus crucial. These three approaches are three different, though entirely complementary, treatments focusing on the same object of study: variation and language change phenomena. Sociolinguistics inevitably tends towards both a theoretical and methodological integration, despite the plurality existing nowadays. This integrationalist tendency has become patent in the attempts of sociolinguists to adapt themselves to those aspects and artefacts of human behaviour, such as social class, sex, age, race, ethnicity, social networks, social groups, attitudes, identity, politics, ideology, etc., as well as of human geography that affect linguistic variation and communication in general.